EL USO DE LOS PRONOMBRES PERSONALES EN EL DISCURSO DEL PROFESOR DE INGLÉS COMO L2 - Torreblanca López, María del Mar (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract L2 teacher discourse has a triple function: it is the subject the students are learning, it is language used in the classroom to communicate and it is the model for students to imitate. For some authors it is a type of modified discourse like caretaker speech, mother talk or foreigner talk. Teachers simplify their speech, trying to offer comprehensible input to their students in order to favour their acquisition, yet, not all the deviations found in this discourse are due to a simplification at different levels. Some processes make this variety more complex. The need for students and teachers to save face and the preservation of a harmonious interactive atmosphere in the classroom could account for this complexity. In this paper we will concentrate on the special use of pronouns by teachers in the setting tasks, correcting work and offering explanations in a 30 hour corpus of EFL and ESL classes. Brown & Levinson ‘s Politeness Theory (1978, 1987) will be the theoretical framework used to account for this use of language.